(untitled) (Heritage, 2026)
The main subject of the research in the paper is the analysis of the models used by Serbian government in the period from the First Serbian Rebellion to the Second World War to suppress prostitution as a social and medical problem. Within the analyzed time period, the state used different models, from the one that criminalized prostitution to the one that tolerated it as a "necessary evil". However, whichever method the state had chosen, the effects were weak, prostitution still existed, as well as venereal diseases. Therefore, investigating prostitution as a phenomenon that is still present in society today and for which the state still seems to be looking for an adequate model of response, it is necessary to look back into the legal past in order to see which of the several used models proved to be the best in practice